The Adolescent Microbiome–Gut–Brain Axis: Development, Mechanisms, and Translational Perspectives - Dolores B. Vazquez-Sanroman; Liam Longaberger; Alondra Chance; Michael Anderson; Nedra Wilson; Gerwald Koehler (Nutrients, 2026)
Background: Adolescence represents a pivotal, yet understudied, developmental window in which maturation of the gut microbiome, neural circuits, endocrine systems, and behavioral processes converge. Although early-life microbiota–gut–brain interactions are well established, emerging evidence demonstrates that adolescence constitutes a “second sensitive period” during which microbial composition, metabolic output, and immune function undergo substantial restructuring. These microbial transitions parallel key neurodevelopmental events, including synaptic pruning, dopaminergic refinement, and heightened neuroendocrine activity, suggesting a coordinated microbiome–gut–brain developmental program. Cross-species comparisons reveal broad alignment between rodent and human adolescent milestones, though inconsistencies in development staging present challenges for translational interpretation. Environmental influences—such as diet, stress, antibiotics, and physical activity—further modulate microbial and neural maturation during this period, with potential long-term consequences for cognition, emotion, and stress responsivity. Mechanistically, microbial metabolites, vagal pathways, immune mediators, and steroid hormone interactions constitute key interfaces linking the gut microbiome to adolescent brain function. Recognizing adolescence as a mechanistically rich and plastic phase of gut–brain co-development underscores the need for harmonized methodological approaches and developmental alignment frameworks. Methods-Results: This review synthesizes ontogenetic, mechanistic, and translational evidence to highlight conserved microbiome–gut–brain pathways and identifies opportunities for targeted interventions during this critical developmental stage.